Perancangan Sistem Enterprise Resource Planning (ERP) Modul Inventory dan Human Resource pada Yayasan Panti Jompo - Abdillah, Mhd Dzaky (Universitas Harapan Medan, 2022)
Some nursing home foundations still have problems, especially in the data, information, and reports section. One of them is an error in data input so that the information becomes inaccurate. ERP (Enterprise Resource Planning) is a method that can be used in building systems to solve these problems. In ERP (Enterprise Resource Planning) there are many modules that are the reference in building the system. The modules used in this research are the Inventory module and the Human Resource module. The Inventory module is used to manage asset data, incoming goods or orders, and outgoing goods. The Human Resource module is used to manage employee data, working hours and attendance, payroll, recruitment, and acceptance of new employees. This system was built using the Code Igniter 4 framework to simplify and make the system more structured in the process. There are five actors involved in this system, namely the central admin, officers, nurses, managers, and patient guardians. Each of these actors has different access and tasks. The results of this study are a system that can facilitate employee data collection, knowing the condition and status of patients, data collection of goods, and asset data management.